Detrimental effects of verapamil in patients with primary pulmonary hypertension. Issue 1 (July 1984) - Packer, M; Medina, N; Yushak, M; Wiener, I
Abstract : Calcium channel blockade provides a logical approach to the treatment of pulmonary hypertension because these drugs exert direct vasodilator effects in the highly constricted pulmonary circulation. To determine the effectiveness of verapamil in the treatment of primary pulmonary hypertension the haemodynamic effects of the drug were evaluated in seven patients with this disorder; 10 mg was given intravenously to six patients and 120 mg orally to one patient. Verapamil produced a 20% decline in pulmonary vascular resistance and a 27% decrease in mean pulmonary arterial pressure without significant changes in systemic vascular resistance. One patient who received verapamil 480 mg orally daily for three months showed sustained haemodynamic and clinical improvement. Concomitant with its beneficial effects on the pulmonary circulation, however, verapamil produced a pronounced decrease in right ventricular stroke work index (42%) and increase in right ventricular filling pressure (50%), indicating a direct depressant effect of the drug on right ventricular function. In one patient these cardiodepressant effects were sufficiently pronounced to produce severe hypotension and cardiac arrest. In conclusion, although verapamil appears to exert preferential vasodilator effects on the pulmonary circulation, its negative inotropic effects may be particularly detrimental to patients with primary pulmonary hypertension who have pre-existing right ventricular dysfunction; hence, treatment with verapamil is not recommended in such cases.